Natural Photodynamic Activity of 5-Aminolevulinic Acid Produced by E. coli Overexpressing ALA Synthase from Bradyrhizobium japonicum - Chon, S.U. (Gwangju Institute of Science and Technology, Gwangju,), E-mail: chonsu@lycos.co.kr; Jung, S. (Kyungpook National University, Daegu, Republic of Korea); Boo, H.O. (Dongshin University, Naju, Republic of Korea); Han, S.K. (Jeonju University, Jeonju, Republic of Korea) (Korean journal of crop science, 2006)
The present study was conducted to determine plant growth and physiological responses of corn, barnyardgrass, and soybean to ALA (5-aminolevulinic acid). ALA effect on early seedling growth of test plants was greatly concentration dependant, suggesting that it inhibits at higher concentrations. No significant difference in herbicidal activity of two types of ALA on plant height and weight of test plants was observed. Barnyardgrass was the most sensitive to ALA and followed by corn and soybean, indicating that both crop plants were less affected by ALA concentration as well as different growth stages than barnyardgrass.